REPRESENTASI KESANTUNAN DALAM NOVEL ANNE OF GREEN GABLES: KAJIAN PRAGMATIK - Ratnaningtyas Lestari; M.R. Nababan; Djatmika Djatmika (Prasasti: Journal of Linguistics, 2020)
This article aims to find and explain the politeness strategies found in the novel Anne of Green Gables. Politeness strategy applied in prohibiting becomes the topic of this study. This study uses Brown and Levinson's politeness strategy consisting of bald on record, off record, positive, and negative strategies. This study is qualitative descriptive. The source data of the study is the Anne of Green Gables novel and the data is characters’ speeches in the novel that accommodates the prohibiting politeness. The data is classified according to Brown and Levinson's politeness strategies, they are bald on record, off record, positive, and negative strategies. The results show that the direct politeness strategy (bald on record) is the most commonly found, then the positive politeness strategy, the indirect politeness strategy and also the negative politeness strategy. It shows that between characters often use direct prohibiting to convey their wants and it also makes the receiver understands it easier. Moreover, using a positive politeness strategy show a close relationship between the speaker and the receiver.